The Implications of Ownership Structure for the choice of Entry Modes: the Empirical Study of Foreign Entries made by Chinese Firms Between 2010 and 2013 - Lu, Jingting (2013)
This dissertation draws on four theories to analyse the linkage between firms’ attributes, from the ownership structure perspective, and their internationalisation strategies by integrating international business research with ideas of corporate governance and institutional analysis. Three hypotheses in respect to institutional ownership, state ownership and insider ownership have been developed and examined. Besides, its contribution also lies in assisting Chinese firms to better understand their counterparts overseas behavious and sheding light on how firms from emerging markets behave in choosing entry modes. Based on a sample of 338 foreign market entries by 267 non-diversified Chinese firms from assorted industries and secotrs between 2010 and 2013, the findings indicate that the greater equity ownership by institutional shareholders and insiders is positively associated with a preference for full-control entry modes. By contract, state ownership has nagative but unstable implication to the choice of full-control modes. The resrults from empirical study provide new evidence to support the pervasive influence from ownership structure to firms’ strategic choice in the international arena.